2005
DOI: 10.1111/j.1742-6723.2005.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with walkout of patients from New South Wales hospital emergency departments, Australia

Abstract: After adjusting for triage category (urgency of presentation) and triage time, patients from lower socioeconomic backgrounds and those without private health insurance coverage were more likely to leave ED without treatment. These results have important implications for Health Services. Future strategies aimed at minimizing walkouts from public hospital ED should prioritize and target factors identified in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 36 publications
5
46
2
2
Order By: Relevance
“…It causes decreased compliance with clinical guidelines, decision-making errors through focus on the politics of transfer rather than quality of care, and an increase in the quantity of adverse events. ED overcrowding is also conducive to extensive waiting times that cause patients to leave without being assessed (Holroyd et al, 2004;Diercks et al, 2006;Hendrie et al, 2007;Mohsin et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…It causes decreased compliance with clinical guidelines, decision-making errors through focus on the politics of transfer rather than quality of care, and an increase in the quantity of adverse events. ED overcrowding is also conducive to extensive waiting times that cause patients to leave without being assessed (Holroyd et al, 2004;Diercks et al, 2006;Hendrie et al, 2007;Mohsin et al, 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Like other studies, we found that patients who LWBS present with conditions of lower urgency, are more likely to be younger patients, to be male, to have arrived without assisted transport, to have self-referred, to be of indigenous Australian background, to be from non-English-speaking backgrounds, and to have arrived in the evening. 2,[15][16][17] The relationship of LWBS with indigenous status is important. Based on data from the Australian Bureau of Statistics, Victoria has a low level of indigenous population compared to the overall data for Australia; 18 however, the issues contributing to higher risk of LWBS for this patient population will need further exploration to tailor effective interventional strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other studies, we found that there was no difference in SES and that those who LWBS were less likely to be of lower SES. 2,16 We used the SEIFA IER and the SEIFA Index of Education and Occupation, whereas Mohsin et al, 16 who found an association with lower SES, used the SEIFA index of relative socioeconomic disadvantage. The SEIFA indices measure at an area level and Data are reported as n (%).…”
Section: Discussionmentioning
confidence: 99%
“…3 The most common reason for walking out before being seen in EDs in other contexts is dissatisfaction with the waiting time. 23 However, Indigenous patients generally waited a similar time, and often slightly shorter, to be seen as similar non-Indigenous patients. This confirms the findings of the literature review.…”
Section: Indigenous Healthmentioning
confidence: 98%